1713 Reducing Asthma Clinic Attendance Using Postal Survey with Mobile Texting Feedback. (October 2012) - Perrem, LM; Manning, P; O'Neill, MB
Abstract : Background and Aim: Attempting to reduce unnecessary attendances of well patients at outpatient clinics is prudent. This study evaluated the Asthma Control Test (ACT)t and Respiratory Proforma, with feedback through mobile texts, in children with Asthma, to determine attendance at clinic or not. Methods: Patients between 4 and 11 years with a diagnosis of asthma were eligible for inclusion. The parent was surveyed, by ppost, 2 weeks prior to the clinic date and asked to complete the Asthma Control Test (ACT) and a Respiratory Proforma which assessed UACS symptoms, medication usage inclusive of intensification episodes and medical concerns. Mobile telephone numbers were requested. Parents mailed their responses in a supplied stamped envelope supplied. Respondents were divided into 2 categories a) ACT score greater than 19 and a non concerning Respiratory Proforma, who were texted not to attend the clinic but supplied with another outpatient appointment and b) the remainder were texted to attend the clinic. Results: Over 6 clinics the parents of 77 eligible children were surveyed. Fifty eight (75%) replied of whom 38 (66%) were well and did not attend the clinic but rebooked. Of 20 who attended, 6 had new symptoms of UACS and 3 had pneumonia. Of 19 who did not reply 7 came to clinic with completed questionnaires, 5 had good control. Ten did not attend the clinic or complete the questionnaire. Conclusion: Asthma care through postal survey with mobile text feedback is an option in the outpatient setting.